Palladium-Catalyzed Cyclization of Cyclopropyl-Substituted 1,6-Enynes to 5.7-Bicyclic Trienes or Monocyclic Trienes Depending upon the Leaving Group - Oh, Hye Mi; Sim, So Hee; Lee, Sang Ick; Kim, Jisu; Chung, Young Keun (Synlett, 2012)
Palladium-catalyzed cyclization of cyclopropyl-substituted 1,6-enynes proceeded in two ways depending on the presence or absence of a leaving group. In the presence of the leaving group, 5.7-bicyclic trienes were obtained as the sole products; in the absence of the leaving group, monocyclic trienes were isolated.
Keywords: palladium; enynes; vinyl cyclopropanes; seven-membered rings; bicyclic compounds